(untitled) (Journal of the College of Basic Education, 2022)
This study attempts to unveil an important theme and stylistic feature that characterizes the poetry of Al-Khansaa, whose features became clear and its mysteries were revealed through the poet’s investment of a special language that characterized her poetry in the lamentation of her two brothers.As this study contributed to shedding light on the poetess’ creative ability and her special linguistic skill in investing language data and diving into the seas of words to produce an elegiac poetic lexicon for the poetess to translate her overflowing feelings and her extended grief on the map of Arabic poetry to draw features of creativity for that sad, crying woman who is skilled at embodying her pain and burning.